Vibrotactile feedback for correcting aerodynamic position of a cyclist - Peeters, T.; Vleugels, J.; Garimella, R.; Truijen, S.; Saeys, W.; Verwulgen, S. (Journal of Sports Sciences, 2020)
Guidance to maintain an optimal aerodynamic position is currently unavailable during cycling. This study used real-time vibrotactile feedback to guide cyclists to a reference position with minimal projected frontal area as an indicator of aerodynamic drag, by optimizing torso, shoulder, head and elbow position without compromising comfort when sitting still on the bike. The difference in recapturing the aerodynamic reference position during cycling after predefined deviations from the reference position at different intensities was analysed for 14 participants between three interventions, consisting of 1) vibrotactile feedback with a margin of error of 1.5% above the calibrated reference projected frontal area, 2) vibrotactile feedback with a margin of 3%, and 3) no feedback. The reference position is significantly more accurately achieved using vibrotactile feedback compared to no feedback (p < 0.001), but there is no significant difference between the 1.5% and 3% margin (p = 0.11) in terms of relative projected frontal area during cycling compared to the calibrated reference position (1.5% margin -0.46 ± 1.76%, 3% margin -0.01 ± 2.01%, no feedback 2.59 ± 3.29%). The results demonstrate that vibrotactile feedback can have an added value in assisting and correcting cyclists in recapturing their aerodynamic reference position.